Lived Experiences of Educators Engaged in Continuing Professional Development in the New Normal: Insights from Seven Countries - Glen P. Cortezano; Rolando V. Maningas; Alberto D. Yazon; Lerma P. Buenvinida; Consorcia S. Tan; Victoria E. Tamban (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2021)
This study focused on exploring and capturing the essence and meaning of the lived experiences of educators engaged in continuing professional development in the new normal. The study followed a qualitative research design and used the transcendental phenomenological processes. Based from the testimonies gathered from the participants from seven different countries- Philippines, USA, Panama, Peru, Pakistan, Nigeria, and Morocco they revealed that as a result of the Continuing Professional Development during pandemic, they have manifested adaptability and innovation to meet the demands of the current situation. With the force transition from face to face interaction to remote learning, they have tried their best to maintain a balance of digital and life skills. Participants also engaged in CPD in order to achieve creativity and resourcefulness to deliver and meet students’ quality learning amidst pandemic. They also considered as blessings and great opportunity the connection and collaboration established with educators around the world during this time of Covid-19. They also achieved the passion for ever-learning mindset and satisfaction through CPD. Participants expressed that mindfulness and wellbeing of teachers should be set as priorities for their engagement to CPD in the new normal. The researcher recommends that the policy makers review and revisit their program for CPD training of the teachers during this period. Heads of the education sectors may also benchmark the CPD Training plan of this study and conduct needs analysis to provide the most appropriate trainings for the teachers based on their needs, skills and interests.